Tolerance and Removal of Four Polycyclic Aromatic Hydrocarbon Compounds (PAHs) by Black Soldier Fly (Diptera: Stratiomyidae). Issue 3 (25th April 2020) - Fan, Mingxia; Liu, Nian; Wu, Xiangji; Zhang, Jibin; Cai, Minmin
Abstract: Polycyclic aromatic hydrocarbons (PAHs), as well-recognized toxic chemical, cause the public hazard in environments. Here, we demonstrated the black soldier fly larvae (BSFL) could tolerate the PAHs and reduce their content. Four typical PAHs (1.0, 10.0, and 100.0 mg/kg), naphthalene, fluorene, phenanthrene, and pyrene, were individually spiked into BSFL conversion systems. The parameters for larval growth, conversion process, and PAHs removal were determined in spiked group and no-spiked control. The results show that the larval development time (19.7–21.0 d) in the half of PAH groups was significantly longer by 2–4 d than those in the control, while the relative growth rates (1.88–1.99% per day) in the majority PAH groups were lower. The larval mortalities (0–2.83%), harvest yields (80.20–85.91 g), conversion rates (14.71–15.83%), and eclosion rates (60.27–82.67%) in almost all of PAH groups did not significantly different from those in the control. The four PAHs potentially delayed the development time of BSFL, slowed the larval growth, and lower waste reduction rates, but these influences were slight and might be caused by the inhibition of PAHs to microbial activity. The BSFL-mortalities, conversion rates, yields, and eclosion rates were not significantly affected by the PAHs. Furthermore, BSFL effectively removed 34.1–84.2% of PAHs from subtracts in 18–21 d. The removal of PAHs with low concentration could be easier than those with high concentration by BSFL. The present results provide an alternative strategy to treat the waste contaminated by PAHs and elucidate the effect of PAHs on insects in the environment.